Analisis Retorika Dakwah Tuan Guru Haji Muhammad Taufiq Ansori melalui Media Youtube - heriadi (Institut Agama Islam (IAI) Nurul Hakim, 2024)
There are many aspects that make a preacher popular among mad'u, one of which is rhetoric. Rhetoric is the style of conveying the message conveyed by the da'i to the mad'u. By delivering a good message, it will lift the spirit and status of the preacher. This research aims to determine Tuan Guru Muhammad Taufiq Ansori's rhetorical style, including language style, voice style and body movements. The method used in this research uses qualitative research methods with a content analysis approach. Data on techniques for collecting, observing or watching existing videos have been uploaded on the YouTube channels of Tuan Guru Muhammad Taufiq Ansori and Tuan Guru Muhammad Atiq. Then analyze the words that contain the application of style, voice and gestures. The data source is Tuan Guru Muhammad Taufiq Ansori's YouTube channel itself and supporting knowledge such as books, journals, the internet or other references that discuss rhetorical style. From this research, results were obtained which showed that Mr. Teacher Muhammad Taufiq Ansori applied a rhetorical style very well in his lectures. First, the language style used tends to use words that are gentle, polite, do not cause provocation, and create a peaceful atmosphere. Apart from that, the language used is firm and not long-winded. Second, it is a rhythmic sound style, found in a flat tone when explaining history with moderate vocals so that it touches the listener. Third, apart from the language style and voice style, Mr. Teacher Muhammad Taufiq Ansori also uses body movements such as body posture and eye gaze, dressing politely and neatly, mimicking the face, and hand movements. The results obtained from this research can be a reference for preachers to preach in spreading Islamic teachings.